From Bestiaries to Pokédexes: Ordering the Otherworldly in Japan’s Monster Traditions - Ann Marie L. Davis (Education About Asia, 2026)
This article traces the enduring presence and transformation of Japan’s monsters—from medieval picture scrolls and Edo-period bestiaries to contemporary manga—emphasizing their role as symbolic figures and creative devices. By focusing on the Japanese legend, the Night Parade of One Hundred Demons (Hyakki Yagyō)—a nocturnal procession in which a multitude of monsters march through the streets—as a recurring visual framework, the discussion shows how yōkai and other monsters have been continually reimagined to reflect shifting cultural functions, serving as tools of satire, imagination, and social commentary. Despite their changing forms and meanings, these monsters consistently act as catalysts for artistic invention, embodying a playful—yet sometimes terrifying—engagement with the mysterious, the uncontrollable, and the unknown. Their persistence in today’s manga underscores a continuing human desire to impose order on, and simultaneously revel in, encounters with the otherworldly.
Keywords: yokai; monsters; manga; Japan; folklore